2017
DOI: 10.1080/10790268.2017.1281373
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bacterial epidemiology and antibiotic resistance among veterans with spinal cord injury/disorder over the past 9 years

Abstract: GNB are isolated frequently in Veterans with SCI/D and have demonstrated increasing resistance over the past 9 years. Priority should be given to controlling the spread of resistant bacteria in this population. Knowledge of local and regional epidemiologic trends in antibiotic resistance in patients with SCI/D may improve appropriate antibiotic prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
(50 reference statements)
2
27
0
Order By: Relevance
“…[1][2][3]12 Furthermore, asymptomatic bacteriuria is very common in SCI-related NLUTD, and avoidance of overtesting and treating asymptomatic bacteriuria is critical to avoid antibiotic resistance. [1][2][3]10,[21][22][23] Identifying symptomatic UTIs is challenging for most clinicians in the setting of NLUTD. Figure 1 defines significant bacteriuria and outlines an office approach to diagnosis and management of symptomatic UTI.…”
Section: Urinary Tract Infectionmentioning
confidence: 99%
“…[1][2][3]12 Furthermore, asymptomatic bacteriuria is very common in SCI-related NLUTD, and avoidance of overtesting and treating asymptomatic bacteriuria is critical to avoid antibiotic resistance. [1][2][3]10,[21][22][23] Identifying symptomatic UTIs is challenging for most clinicians in the setting of NLUTD. Figure 1 defines significant bacteriuria and outlines an office approach to diagnosis and management of symptomatic UTI.…”
Section: Urinary Tract Infectionmentioning
confidence: 99%
“…Numerous studies have reported that elderly and war veterans often suffer from multiple syndromes with inflammatory phenotypes and are more susceptible to resistance against a large number of antibiotics [16], [17], [18]. Veterans have been reported to be resistant to amoxicillin, β-lactams, fluroquinolones, methicillin and most importantly the carbapenem group of antibiotics [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…3 Overtreatment of ASB promotes the development of multi-drug-resistant organisms, and other complications of antibiotic use such as Clostridioides difficile infection; both of these are common and burdensome in the SCI/D population. [4][5][6][7] Antibiotic stewardship programs, or initiatives aimed to promote the appropriate, safe, and effective use of antibiotics, aim to mitigate these complications, and have been recognized globally as an important public health topic. 8 There are still important knowledge gaps that must be filled before effective antibiotic stewardship programs can be implemented in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described the diagnostic challenge of UTI after SCI/D given the atypical signs and symptoms of infection and the high prevalence of ASB in the population in a narrative review 3. Overtreatment of ASB promotes the development of multi‐drug‐resistant organisms, and other complications of antibiotic use such as Clostridioides difficile infection; both of these are common and burdensome in the SCI/D population 7. Antibiotic stewardship programs, or initiatives aimed to promote the appropriate, safe, and effective use of antibiotics, aim to mitigate these complications, and have been recognized globally as an important public health topic 8…”
Section: Introductionmentioning
confidence: 99%